Motor Skill Training Effects on Coordination and Reaction Time in 6 - 16 Years Old Children with ASD and DS - Pano, Dr. Genti; M. Sc. Denis Nuriu,; Doc. Anduela Lile, (American Scientific Research Journal for Engineering, Technology, and Sciences, 2021)
ASD is becoming one of the most common pediatric cases in the world and several research studies report an increased ASD prevalence. DS is a genetic disorder caused when abnormal cell division results in an extra full or partial copy of chromosome 21. Main objective of this study was to investigate motor skill training effects on coordination and reaction time in 6 - 16 years old children with ASD and DS. 21 children with ASD 20 children with DS became part of this study. 3 tests were used to evaluate the motor skills: 1. Grooved Pegboard Test (mod 7446). 2. Box and Blocks Test. 3. Ruler Drop Test. A 12 weeks exercise training program 3 times/week, including; cardiovascular exercise, short and fast jogging, flexibility exercises and gross motor control exercises. Each group was assigned to an exercise station (total 5 stations), with a total of 20 min. Repeated measures Motor skill training had a positive effect on eye-hand-subject coordination and reaction time in the subjects participated in this study showing that this type of exercise, if possible, can and should be included in the overall rehabilitation therapy for this category.